Network Optimization Algorithm Based on Power Control and Channel Assignment - Yue Liu; Xiaolei Guo; Xun Zhang (Dianxin kexue)
WLAN has been massively deployed in various places.However，the poor user perception of network quality，or even dropping line，unable to connect to the network and other issues.For this case，a network optimization algorithm based on power control and channel assignment was proposed.The algorithm uses the method of power control and channel assignment to optimize the WLAN in a specific range，maximize the effective bandwidth of WLAN，and ensure the balance of network load at the same time.Simulation experiments show that the network optimization algorithm of the power control and channel assignment has achieved the aim of improving network performance.